Non-coherent distributed space–time coding techniques for two-way wireless relay networks - Alabed, Samer; Pesavento, Marius; Klein, Anja (Signal processing, 2013)
To overcome the overhead involved with channel estimation, several non-coherent distributed space–time coding (DSTC) strategies for two-way wireless relay networks (TWRNs) using the amplify-and-forward and the decode-and-forward protocol have been recently proposed that do not require channel state information (CSI) at any node to decode the information symbols. In this paper, novel differential DSTC strategies for TWRNs using the two- and three-phase protocol are proposed. In our transmission schemes, the relays do not waste power to transmit information known at the respective destination nodes. This is achieved by combining the symbols from both terminals received at the relays into a single symbol of the unaltered constellation. Furthermore, in our strategies, the direct link between the communicating terminals can be naturally incorporated to further improve the diversity gain. Simulations show a substantially improved performance in terms of bit error rate (BER) of the proposed strategies as compared to the existing strategies. ► Differential DSTCs for TWRNs using the two- and three-phase protocol are proposed. ► The proposed strategies do not require CSI at the terminals or relays. ► The proposed strategies provide more coding gain as compared to the other known strategies. ► The proposed strategies allow the terminals to use the direct link between them. ► Relays do not waste power to transmit redundant information by combining the received symbols.